Palynological Study for the Species of the Genus Echinops L. (compositae) in Iraq - Al-Musawi , Ali H.; A. Aliwy, Sukeyna (Iraqi Journal of Science, 2023)
The paper comprise comparative palynological study of (11) species belong to the genus Echinops L. in Iraq i.e( E.armatus Boiss. & Hausskn ، E.bicolor Nabelek. ، E.cephalotes DC., E.haussknetchii Boiss. ، E.mosulensis ، Rech. ،E.nitens Bornm. ، E.orientalis Trautv., E.parviflorous BOISS & BUHSE ،E.spinossisms Turra . ، E.tenuisectus Rech. ، E.viscosus DC.، Pollen grain were found to be Tricolporate and with spherical shaped ,in polar view the grain found to be Interangular , while in equatorial view the grain found to be ellipsoid .